The prospective evaluation of malnutrition in hospitalized children in a pediatric urology unit - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: Malnutrition has been reported to be a rather common health problem in hospitalized children and it is recommended to be evaluated in these conditions. The objective of this prospective trial was to evaluate the nutritional status of hospitalized pediatric urology patients and find the prevalence of malnutrition in this specific subgroup of patients. Patients and Methods: All subsequent children between 1 and 18 years old who were hospitalized between January 2018 and January 2019 in the pediatric urology unit of a referral university hospital were included into the study. STRONGkids questionnaire was used to assess the nutritional status of the children. Malnutrition was evaluated according to anthropometric measurements based on the computer programs developed by the World Health Organization (WHO). Results: A total of 76 patients were included in the study. The mean age of the patients was 8.84 +/- 4.23; mean height was 121.03 +/- 22.49 cm; mean weight was 27.8 +/- 13.41 kg. Malnutrition risk, according to STRONGkids screening tool was high in 1 patient, medium in 8 patients and low in 67 patients. According to anthropometric measurements, 6 patients (7.9%) and 25 patients (32.9%) had acute and chronic malnutrition, respectively. Conclusion: The current prospective trial suggested that malnutrition is a significant issue also for hospitalized pediatric urology patients.
Keywords: Malnutrition; Pediatric Urology; STRONGkids; Hospital; SCREENING TOOL; PREVALENCE; NUTRITION; RISK; IDENTIFICATION; TURKISH; NURSES